Performance Enhancement of Photovoltaic Systems Using Parrot Optimization Algorithm-Based Optimal Control Scheme - Alqahtani, Ayedh H.; Hasanien, Hany M. (2024 6th International Conference on Smart Power & Internet Energy Systems (SPIES), 2024)
This paper presents an optimized control strategy for enhancing the low-voltage-ride-through (LVRT) capability of photovoltaic (PV) systems. The proposed method employs a proportional-integral (PI) controller, which is designed using the Parrot Optimization Algorithm (POA). The PV system is connected to the grid via a DC boost chopper and a grid-side inverter. The incremental conductance method is applied to track the maximum power of the PV system. A cascaded control strategy is implemented to control the grid-side inverter. The effectiveness of the POA-PI controller is tested under various symmetrical and asymmetrical fault conditions, demonstrating significant performance improvements. The results are compared with those obtained from a genetic algorithm-PI control system. Numerical simulations are carried out using PSCAD/EMTDC software, illustrating the robustness of the proposed approach.